2023
DOI: 10.3233/adr230007
|View full text |Cite
|
Sign up to set email alerts
|

Current Diagnostic Pathways for Alzheimer’s Disease: A Cross-Sectional Real-World Study Across Six Countries

Abstract: Background: Diagnostic pathways for patients presenting with cognitive complaints may vary across geographies. Objective: To describe diagnostic pathways of patients presenting with cognitive complaints across 6 countries. Methods: This real-world, cross-sectional study analyzed chart-extracted data from healthcare providers (HCPs) for 6,744 patients across China, France, Germany, Spain, UK, and the US. Results: Most common symptoms at presentation were cognitive (memory/amnestic; 89.86%), followed by physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The parallel qualitative study performed 32 revealed that a higher rate of diagnosis among patients presenting to a specialist versus a PCP (∼60% vs. ∼30%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parallel qualitative study performed 32 revealed that a higher rate of diagnosis among patients presenting to a specialist versus a PCP (∼60% vs. ∼30%).…”
Section: Discussionmentioning
confidence: 99%
“…The advisory boards noted that symptomatic patients with a negative blood test still need to be referred, as AD is not the only cause of cognitive impairment (although the most common 43 ). Data suggesting that many patients have inconclusive outcomes such as "watch and wait" 32 support the role of a simple BBBM test to detect amyloid pathology and create a consistent and efficient pathway to confirmatory PET/CSF testing.…”
Section: Unmet Diagnostic Need To Facilitate Timely Detection and Tre...mentioning
confidence: 98%
See 1 more Smart Citation
“…4 Remaining sample size after removal of 5 intermediate cases. 5 Site-speci c cutoffs identi ed 3 Aβ positive and 3 Aβ negative participants in the intermediate "gray zone" (6/50 = 12%).…”
Section: Cross-validation Of P-tau217 In the Butler Map Test Cohortmentioning
confidence: 99%
“…The recent Food and Drug Administration (FDA) approval of amyloid-lowering immunotherapies, such as aducanumab and lecanemab, necessitates the optimization of screening techniques for Aβ pathology, as biomarker con rmation of Aβ status is required prior to treatment (3,4). This important requirement represents a major barrier to treatment access for many patients due to current reliance on invasive and expensive positron emission tomography (PET) or cerebrospinal uid (CSF) testing (5), and may compound existing racial and ethnic inequalities in AD treatment (6-9). The development of a minimally invasive and costeffective screening method to facilitate early detection and intervention is, therefore, of high clinical importance in expanding equitable access to new and forthcoming treatments for early AD (1,10).…”
mentioning
confidence: 99%